2015
DOI: 10.1016/j.cell.2015.04.050
|View full text |Cite
|
Sign up to set email alerts
|

PQBP1 Is a Proximal Sensor of the cGAS-Dependent Innate Response to HIV-1

Abstract: Summary Dendritic cells (DCs) play a critical role in the immune response to viral infection through the facilitation of cell intrinsic antiviral activity and the activation of adaptive immunity. HIV-1 infection of DCs triggers an IRF3-dependent innate immune response, which requires the activity of cyclic GAMP synthase (cGAS). We report the results of a targeted RNAi screen utilizing primary human monocyte-derived DCs (MDDCs) to identify immune regulators that directly interface with HIV-1-encoded features to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
194
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(199 citation statements)
references
References 38 publications
5
194
0
Order By: Relevance
“…Western blotting revealed robust expression of the cytoplasmic DNA sensors reported to recognize HIV reverse transcription products, IFI16, DDX41 (49), and cGAS (Fig. 1A, Tzm-bl CON), as well as PQBP1, which was recently identified as an adaptor between HIV-1 DNA and cGAS (50). In contrast, expression of STING, an essential adaptor for innate signaling downstream of cGAS (27,51,52), was weak or undetectable on the protein level (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Western blotting revealed robust expression of the cytoplasmic DNA sensors reported to recognize HIV reverse transcription products, IFI16, DDX41 (49), and cGAS (Fig. 1A, Tzm-bl CON), as well as PQBP1, which was recently identified as an adaptor between HIV-1 DNA and cGAS (50). In contrast, expression of STING, an essential adaptor for innate signaling downstream of cGAS (27,51,52), was weak or undetectable on the protein level (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…We next investigated key signaling innate immune pathways upon HIV-1 infection. HIV-1 infection is known to cause phosphorylation of TBK1 and IKKε, which leads to IRF3 activation (Gao et al, 2013; Yoh et al, 2015). The phosphorylation of TBK1, IKKε, and IRF3 was significantly enhanced in THP-1 cells with attenuated NLRX1 expression relative to control cells upon HIV-VSV infection, and this is followed by enhanced STAT1 phosphorylation which is known to be activated by type I IFN (Figure 2F).…”
Section: Resultsmentioning
confidence: 99%
“…In HIV-1 infected cells, PQBP1/cGAS recognizes HIV-1 DNA and generates cyclic cGAMP to activate STING (Gao et al, 2013; Yoh et al, 2015). To investigate the role of NLRX1 in STING-dependent innate immune signal transduction, we first examined the impact of NLRX1 on STING-induced activation of interferon-stimulated responsive element (ISRE)-luciferase reporter, which is known to be activated by STING, TBK1, and IRF3 (Ishikawa and Barber, 2008; Zhong et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many DNA viruses have been reported to trigger STING-dependent activity, including adenovirus, vaccinia virus and papilloma virus 2,2831 .The importance of the cGAS–STING axis has also been demonstrated for retrovirus infection including HIV 3235 . It is probable that retroviral DNA activates the cGAS–STING axis, although a recent report indicated that retroviral RNA–DNA hybrids can also trigger this pathway suggesting that a wide array of nucleic acid structures may be capable of triggering STING activity 32,33,3638 .…”
Section: Sting Signalling Triggered By Microorganismsmentioning
confidence: 99%